Flexural Behavior of Composite Reinforced Concrete Slabs - A. Adil, Majid; Oday Adnan Abdulrazzaq, Dr. (Iraqi Journal of Civil Engineering, 2017)
The main objective of this study is to get more information about the flexural behavior of composite reinforced concrete slabs using two layer of concrete, first layer is light weight concrete (LWC), and second layer is normal weight concrete (NWC), through an experimental tests carried out on five samples different in their details and the position of the concrete type layer within the slabs. In this study, simply supported slabs subjected to one point load were adopted. The effect of concrete grade for the (LWC) was also studied. The light weight coarse aggregate which that used in this study is the expanded light clay aggregate (LECA). Using this type of light aggregate in concrete leads to reducing the weight of composite concrete slabs about (11.4%-17.5%). In this study, one grade of NWC was used of (25 MPa), while three of grade types were adopted for LWC (25 MPa, 18 MPa, 15 MPa).